Laparoscopically Assisted Anorectal Pull-Through versus Posterior Sagittal Anorectoplasty for High and Intermediate Anorectal Malformations: A Systematic Review and Meta-Analysis. - Yijiang Han; Zhaobo Xia; Shikun Guo; Xiangbo Yu; Zhongrong Li (PLoS ONE)
Objective Anorectal malformations (ARMs) are one of the commonest anomalies in neonates. Both laparoscopically assisted anorectal pull-through (LAARP) and posterior sagittal anorectoplasty (PSARP) can be used for the treatment of ARMs. The aim of this systematic review and meta-analysis is to compare these two approaches in terms of intraoperative and postoperative outcomes. Methods MEDLINE, Embase, Web of Science and the Cochrane Library were searched from 2000 to August 2016. Both randomized and non-randomized studies, assessing LAARP and PSARP in pediatric patients with high/intermediate ARMs, were included. The primary outcome measures were operative time, length of hospital stay and total postoperative complications. The second outcome measures were rectal prolapse, anal stenosis, wound infection/dehiscence, anorectal manometry, Kelly's clinical score, and Krickenbeck classification. The quality of the randomized and non-randomized studies was assessed using the Cochrane Collaboration's Risk of Bias tool and Newcastle-Ottawa scale (NOS) respectively. The quality of evidence was assessed by GRADEpro. Results From 332 retrieved articles, 1, 1, and 8 of randomized control, prospective and retrospective studies, respectively, met the inclusion criteria. The randomized clinical trial was judged to be of low risk of bias, and the nine cohort studies were of moderate to high quality. 191 and 169 pediatric participants had undergone LAARP and PSARP, respectively. Shorter hospital stays, less wound infection/dehiscence, higher anal canal resting pressure, and a lower incidence of grade 2 or 3 constipation were obtained after LAARP compared with PSARP group values. Besides, the LAARP group had marginally less total postoperative complications. However, the result of operative time was inconclusive; meanwhile, there was no significant difference in rectal prolapse, anal stenosis, anorectal manometry, Kelly's clinical score and Krickenbeck classification. Conclusion For pediatric patients with high/intermediate anorectal malformations, LAARP is a better option compared with PSARP. However, the quality of evidence was very low to moderate.